(untitled) (Brazilian Journal of Behavioral and Cognitive Therapy, 2020)
This study investigated the possible role of class formation on the transfer of stimulus function in the control of different responses of problem solving in Rattus norvegicus. The problem consisted of a task of pushing a cube, climbing the cube, and pulling a chain. All subjects were trained in the test skills. The PS group (pulling the spot) underwent a spot pull training, the subject NPS1 of the NPS group (not pulling the spot) was trained to sniff the spot and NPS2 did not have additional training. All the subjects solved the task. The training of pulling the spot did not prove to be critical to solve the problem and did not favor the performance of subjects (PS1 and PS2) who underwent this procedure. The data do not support that problem solving of the insight type can be exclusively attributed to class formation between stimuli and responses.